Stand Up for Chronic Obstructive Pulmonary Disease - Coll, Fiona (Curtin University, 2023)
The PhD program of research aimed to explore sedentary behaviour in people with chronic obstructive pulmonary disease (COPD). This research included two systematic reviews and meta-analyses and a single-case experimental design (SCED). The studies were designed to investigate measurement of sedentary behaviour and strategies to reduce time spent in sedentary behaviour in people with COPD. The findings were sedentary behaviour in people with COPD was difficult to reduce though qualitative findings revealed positive lifestyle changes.